The impact of school environment, student attitude and peer influence towards aggressive behaviour among secondary schools students in Johor Bahru - Azizi Yahaya; Zeliha Hj Mohamad Ali; Faizah Binti Idris; Ismail Ma’akip; Halimah Ma’alip; Hanun Ahmad; Nordin Ajmain; Pg. Razmahayati Pg. Hj. Mahmud (Human Resource Management Academic Research Society (HRMARS), 2023)
The objective of the study is to identify the significant differences between school environment, student attitude and peer influence among among secondary schools students in Johor Bahru according to gender. Secondly, this research is to identify school environment, student attitude and peer influence are predictors to aggressive behavior among students among secondary schools students in Johor Bahru. About 260 questionnaires were distributed at random stage to aggressive student from secondary one, two and four with total of 260 students. The instrument used was the Mooney Problem Check List which was later analysis by the SPSS 26.0 (Statistical Package for Sosial Science). T-test and regression (stepwise) used to analyse the data. The hypothesis shows that there is no significant difference between aggressive factor and student rate. There is no significant differences on school environment, family background, student attitude, peer influence and psychology according to gender. Thus, this research found that school environment, student attitude and peer influence are predictor to aggressive behaviour among student. The study suggested that the school should identify aggressiveness culture among the students and should implement the peer program therefore the problems will be decrease